Learning Tool for Robotics Basic Programming Based on Contextual Teaching and Learning to Improve Problem-Solving Skills - Muhamad Syariffuddien Zuhrie; Munoto Munoto; I Gusti Putu Asto B; Lilik Anifah; Nur Hasanah (Faculty of Engineering, Universitas Negeri Yogyakarta, 2020)
In the robotics program design basic course, it is very essential to be able to construct programming and then translate it into the language. If there is a design error in the algorithms and mistakes in the flowchart or an error in translating it into a programming language, the application software would be unable to work. The objectives of this study are to develop the basic teaching module for Robotics Programming and to implement robotics courses oriented on contextual teaching and learning to enhance university students' problem-solving skills. This study was designed with pre-action, action and reports procedures. 4D development was employed in the software development process. Implementation processes cover four phases: identifying, planning, creating, and disseminating. The findings suggested that contextual teaching and learning enable students to be actively engaged in the learning process encourage and motivated more active students' activities and promote creativity.